2008
DOI: 10.1080/00986280802374419
|View full text |Cite
|
Sign up to set email alerts
|

Ways of Writing: Linguistic Analysis of Self-Assessment and Traditional Assignments

Abstract: Scholars of teaching and learning have endorsed self-assessment assignments as a way to encourage greater reflection by students. However, no studies to date have compared writing in self-assessment with traditional academic assignments. We performed a quantitative text analysis of students' language in self-assessment versus traditional assignments from 3 courses. Self-assessment assignments included more references to cognitive words (i.e., words related to insight) than traditional academic assignments. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Similarly, tense variables and common verbs were also included in the analysis as patterns emerging in prior studies have shown that reflective writing focuses on actions through verb use and, in particular, future behaviour derived from present observations [20]. In addition, words related to cognitive processes, including insight and exclusive terms, are commonly observed terms in self-reflections [30], and hence, were also included in the study. Words with greater than six letters were also analyzed as their use indicates the use of complex language [35].…”
Section: Linguistic Analysis Of Self-reflectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, tense variables and common verbs were also included in the analysis as patterns emerging in prior studies have shown that reflective writing focuses on actions through verb use and, in particular, future behaviour derived from present observations [20]. In addition, words related to cognitive processes, including insight and exclusive terms, are commonly observed terms in self-reflections [30], and hence, were also included in the study. Words with greater than six letters were also analyzed as their use indicates the use of complex language [35].…”
Section: Linguistic Analysis Of Self-reflectionsmentioning
confidence: 99%
“…While prior studies have used LIWC to analyze various forms of students' written assignments, such as critical thinking essays [4], self-introductions [33], and career-related narratives [23], only a few have investigated the linguistic and psychometric terms most commonly present in reflective writing [20,30]. Although LIWC can process word counts associated with 74 linguistic and psychological variables, we incorporate only a subset of these in our textual analysis.…”
Section: Linguistic Analysis Of Self-reflectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peden and Carroll (2008) found that the linguistic analyses distinguished between the words used in different academic assignments. When writing papers that required self-assessment, students used more cognitive words (e.g., 'think', 'consider'), emotion words (e.g., 'happy', 'anxious'), and first-person pronouns (e.g., 'I', 'me') than when writing more traditional term papers.…”
mentioning
confidence: 99%